Body weight in midlife and long-term risk of developing heart failure-a 35-year follow-up of the primary prevention study in Gothenburg, Sweden - Björck, Lena (BMC Cardiovasc Disord, 2015)
BACKGROUND: This study aimed to determine whether midlife obesity predicts heart failure (HF) over an extended follow-up into old age. METHODS: We studied 7495 men (from a population sample of 9,998 men) without HF, who were 47–55 years old when investigated in 1970 to 1973. All participants were followed up for 35 years, or until death, using the Swedish National Inpatient Register (IPR) and the Cause of Death Register. Over follow-up, 1855 men (24.7%) were discharged from hospital or died with a diagnosis of HF. RESULTS: There was a strong relation between obesity and future risk of HF, which was accentuated over the last years of the long follow-up. After adjusting for age, the risk of HF increased stepwise with increasing body mass index (BMI), even in those with a normal BMI (22.5–24.9) The subdistribution hazard ratio (SHR) was 1.20 (95% CI: 1.02–1.39) in men with a normal BMI, 1.29 (95% CI: 1.11–1.50) for a BMI of 25–27.49, 1.50 (95% CI: 1.27–1.77) for a BMI of 27.5–29.99, and 1.62 (95% CI: 1.33–1.97) for a BMI >30. After adjusting for, age, smoking, occupational class, and physical activity, the results were unchanged. CONCLUSION: Obesity in midlife is strongly related to the long-term risk of developing HF extending into old age where the risk is highest. Even normal body weight (BMI <25) was related to an increased risk of developing HF during life. Because overweight and obesity are largely preventable, our findings further emphasize the importance of public health interventions against the development of obesity.